Answer:
26
Step-by-step explanation:
Examples:
1 x 13 = 13
3 x 13 = 39
Second blank:
2 x 13 = 26
Answer:
A+6+A = 20
A = 7
Step-by-step explanation:
J = number of problems Juana completed
A = number of problems Andy completed
J+A=20
J = A + 6
Replace J with A+6 in the first equation
A+6+A = 20
2A +6 = 20
Subtract 6 from each side
2A +6-6 = 20-6
2A =14
Divide by 2
2A/2 = 14/2
A = 7
Answer:
She should have substituted y = 17 - 2x in the first equation
Step-by-step explanation:
3x + 4y = 33
2x + y = 17
y = 17 - 2x
3x + 4(17 - 2x) = 33
3x + 68 - 8x = 33
5x = 35
x = 7
y = 17 - 2(7)
y = 3
x = 7, y = 3
Only one solution
<span>mean: ( 9 + 7 + 6.5 + 7.5 + 7 + 8 + 5 + 6 + 7.5 + 8 ) : 10 = 7.15Variance:(Sigma)² = ( 1.85² + 0.15² + 0.65² + 0.35² + 0.15² + 0.85² + 2.15² + 1.15² + 0.35² + 0.85² ) : 10 ≈ 1.15Answer: C ) 1.15</span>
Answer:
The answer is 4.
Step-by-step explanation:
8/3 ÷ 2/3 = 8/3 x 3/2 = 4